Your Fathers, Where are They? And the Prophets, Do They Live Forever? : A Novel - Eggers, Dave (London Hamish Hamilton an Imprint of Penguin Books, 2014)
In a barracks on an abandoned military base, miles from the nearest road, Thomas watches as the man he has brought wakes up. Kev, a NASA astronaut, doesn't recognize his captor, though Thomas remembers him. Kev cries for help. He pulls at the chain. But the ocean is close by, and nobody can hear him over the waves and wind. Thomas apologizes.
A Novel.
Keywords: Mentally ill -- Hostages -- Imaginary conversations -- Questioning